Methane emission from paddy soil in relation to soil temperature in tropical region - Fazli, Pardis; Che Man, Hasfalina; Mohamed Zawawi, Mohamed Azwan; Md. Shah, Umi Kalsom; Abdul Rahman, Nor Aini; Idris, Azni (Penerbit UTM Press, 2016)
Methane (CH4) is 21 times more powerful as a greenhouse gas than carbon dioxide. Wetlands including flooded paddy fields are one of the major sources for this gas. Paddy fields are responsible for producing 25 to 54 Tg of CH4 annually. Methane emission rate could be affected by several factors such as irrigation pattern, fertilizer type, soil organic matter and soil temperature. Among them, soil temperature is a determining factor which deserves to be investigated. This study performed with the aim of understanding the effect of soil temperature on the methane emission rate from paddy soil in a short period of time (hourly) and long term (during rice growing season). The results of this study suggest that soil temperature could control the amount of methane emission and there is a positive and strong correlation in both soil temperature and methane emission pattern in short period of time. However, in case of long term trend, other factors such as water management and plant age decreased this correlation from 0.768 to 0.528.